Analisis Pengaruh Profitabilitas, Kebijakan Dividen, Inflasi dan Nilai Tukar terhadap Nilai Perusahaan - Annisa Pujiati; Fatmi Hadiani (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The purpose of this research is to determine the effect of profitability, dividend policy, inflation, and exchange rates on firm value. The population of this study is the property, real estate, and building construction sector companies listed on ISSI for the 2014-2018 period. In determining the sample data, this study used a purposive sampling method and obtained a sample of 9 companies. Research data is taken from secondary data, namely performance summary reports and reports on inflation and the US dollar exchange rate. The analytical method used to solve the problem in this research is path analysis using the WarpPLS 7.0 application. From this research, it is found that the lower profitability (ROE) and dividend policy (DPR) has a positive and significant effect on firm value (PBV), inflation has a negative and insignificant effect on firm value (PBV) and the exchange rate (US) has a negative effect. and significant to firm value (PBV).